Charge transfer emission between π- and 4f-orbitals in a trivalent europium complex - Yuichi Kitagawa; Toranosuke Tomikawa; Kota Aikawa; Shiori Miyazaki; Tomoko Akama; Masato Kobayashi; Mengfei Wang; Sunao Shoji; Koji Fushimi; Kiyoshi Miyata; Yuichi Hirai; Takayuki Nakanishi; et al. (Communications Chemistry)
Abstract Photoinduced metal-to-ligand (or ligand-to-metal) charge-transfer (CT) states in metal complexes have been extensively studied toward the development of luminescent materials. However, previous studies have mainly focused on CT transitions between d- and π-orbitals. Herein, we report the demonstration of CT emission from 4f- to π-orbitals using a trivalent europium (Eu(III)) complex, supported by both experimental and theoretical analyses. The Eu(III) complex exhibits an eight-coordination structure, comprising three anionic nitrates and two neutral electron-donating ligands containing a carbazole unit. The diffuse reflectance spectrum of the complex displays an absorption band at 440 nm and time-resolved emission analyses reveal a characteristic emission band at 550 nm. Comparative studies employing a trivalent gadolinium (Gd(III)) complex, alongside quantum chemical analyses, confirm that the observed absorption and emission bands are associated with CT transitions between π- and 4f-orbitals. The observation of CT emission based on the 4f-orbital offers novel insights into the field of molecular luminescence science and technology.